Fabrication of Nickel Oxide Nanowall Network Films at Different Annealing Temperatures for Humidity Sensing Applications - H. Mamat, M.; Parimon, N.; A.R. Abdullah, M.; S. Ismail, A.; F.. Malek, M.; R.W. Ahmad, W.; S. Zoolfakar, A.; B. Suriani, A.; K. Ahmad, M.; Nayan, N.; B. Shameem Banu, I.; Amiruddin, R.; et al. (International Journal of Engineering and Technology, 2018)
Nickel oxide (NiO) nanowall network films were successfully prepared on indium tin oxide (ITO) glass substrates by sonicated sol-gel immersion method using a precursor solution of nickel nitrate hexahydrate. The NiO nanowall network films were annealed at different annealing temperature that ranges from 300 â°C to 500 â°C. The effects of annealing temperature on the structural, optical and humidity sensing properties of NiO nanowall network films were investigated by X-ray diffraction (XRD), field emission scanning electron microscopy (SEM), ultraviolet-visible (UV-vis) spectroscopy and humidity sensor measurement system. The X-ray diffraction patterns revealed that the grown NiO nanowall network films have a crystalline cubic structure. The UV-vis spectra demonstrates that the average transmittance value of all samples in the visible region are high and exceeded 90% transmission. The optical bandgap energy of NiO nanowall network films ranged from 3.76 to 3.77 eV. Results obtained showed that the humidity sensing performance of NiO nanowall network films are very promising and could be tuned by annealing temperatures.Â Â